Comercialização de energia : aprimoramento e eficientização da indústria elétrica - Cunha, Paulo César Fernandes da (2003)
This present research is about energy trading as a improving of electric energy industry. Then this research recovered the critic of a recent evolution from that industry and culminated for the proposition of a simplified model to simulate the comercializator enterprises actions as intermediary of economies transactions between production agents and energy consumption to search satisfaction of their necessities. The priority was the analysis of the competitive strategies in the market from the different agents. Here it was identified the main correlations between the organizations types of comercializate agents and the grade of liberty and maturity in the context of the energy industry. The proposed model of analysis offered consistent results compatible with the economic theory. The model explicated tendencies of the movements of comercializators. Argumenting agent s spectatives giving conditions from to return efficient the market.